A melhora da consolidação da memória induzida por espermidina envolve a ativação da via PI3K/AKT - Fabbrin, Shaiana Beck (2020)
Memory consolidation is a process that depends on specific brain structures, such as the hippocampus, synthesis of new proteins, activation of protein kinases and neurotrophins, such as the brain-derived neurotrophic factor (BDNF). BDNF is considered a key modulator in memory processing, as it promotes modulation of synaptic plasticity and, through its connection to the tropomyosin kinase B (TrkB) receptor, activates intracellular signaling pathways that are involved in the formation of new memories, such as the phosphatidylinositol 3-kinase (PI3K) and protein kinase B (PKB) pathway, also known as Akt. The PI3K/Akt pathway is involved in different physiological processes important for cell maintenance and memory acquisition and consolidation. Spermidine (SPD) is a polyamine present endogenously throughout the central nervous system, and acts as a modulator of ion channels, such as the glutamatergic receptor N-methyl-D-aspartate (NMDAr). The administration of SPD promotes improved consolidation, reconsolidation and persistence of memory in different behavioral tasks in rats. However, the mechanism of action of SPD in the consolidation of memory in the task of contextual conditioned fear is not elucidated. Thus, the objective of the study is to investigate the involvement of the TrkB receptor and the PI3K/Akt pathway in improving SPD-induced memory consolidation. Thus, adult male Wistar rats were trained and tested in the contextual conditioned fear task. Immediately or 6 hours after training, animals received intra-hippocampal infusion of SPD, ANA-12 (TrkB receptor antagonist) or LY294002 (PI3K inhibitor). The infusion of SPD (2 nmol) immediately after training improved, while ANA-12 and LY294002 impaired memory consolidation. ANA-12 (0.3 pmol/site) and LY294002 (5 μg/site), in doses with no effect per se on memory, prevented the facilitating effect of SPD on memory consolidation. The administration of the compounds 6 h after training did not alter the animals' memory. A group of animals were euthanized 30 minutes after training to analyze Akt phosphorylation. The infusion of SPD increased the levels of phosphorylated Akt, and the infusion of LY294002 prevented this increase induced by SPD. Thus, the results of the study suggest the involvement of the TrkB receptor and the PI3K/Akt pathway, as well as the increase in Akt phosphorylation to improve SPD-induced memory consolidation.